Kepastian Hukum Perjanjian Pengikatan Jual Beli terhadap Tanah yang Belum Turun Waris di Kota Padang - Rahmdani, Febry; Mardenis, Mardenis; Andora, Hengki (Universitas Ekasakti, 2023)
The impediment to make a sale act by the ppat because its conditions are not met, of course, will create uncertainty for the parties who conduct the sale. The agreement is a binding agreement. The parties entered into an agreement for binding the sale of the land which has not been inherited depending on several factors such as the buyer needs time to carry out the payment of the sale price while the seller takes time to process the inheritance certificate of the right to the land, the purchaser has paid the purchase price but the unity of the rights to the ground has not yet been made to inherit, and/or payment of income tax (PPh) and customs duties on land and building (BPHTB) have not been issued by the parties. The contract of sale of land that has not been inherited is based on the agreement of the parties, which is then continued with the application for the drafting of an act before a notary, the approval of the law by a notar, the submission and inspection of documents, the verification of certificates of the right to the land, the preparation and drawing of acts, and the signing of the act. The Civil Procedure Act against land not inherited made before a notary has legal certainty, because the notary as a public official authorized to make an authentic act subject to the regulations of the laws and the code of ethics of the office of the notar has ensured the validity of the civil procedure act against land that has not been made in heritage made against him and by referring it to a civil proceeding act against the land noted in the notarial act can provide legal protection to the parties in the event of legal protection of an authoritative act.